2018
DOI: 10.1111/bju.14354
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of asymptomatic calyceal stones

Abstract: Long-term conservative approaches for asymptomatic renal stones are an effective management option with ~60% of renal units remaining on active surveillance in >5 years of follow-up. Appropriate counselling with careful patient selection is advocated, as younger patients and those with evidence of stone growth were found to be at greatest risk of an adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 15 publications
1
39
1
Order By: Relevance
“…[20][21][22] Several studies have reported factors associated with surgical intervention during active surveillance, including male sex, age (£50 years), the rate of stone growth, stone history, and stone size. 3,5,7,15,17 In this study, age £50 years and a history of surgical intervention were significant factors associated with surgical intervention, but not stone size <5 mm. Interestingly, in the present study, the incidence of surgical intervention was low in patients above 50 years of age with asymptomatic renal stones £5 mm and without a history of surgical intervention.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…[20][21][22] Several studies have reported factors associated with surgical intervention during active surveillance, including male sex, age (£50 years), the rate of stone growth, stone history, and stone size. 3,5,7,15,17 In this study, age £50 years and a history of surgical intervention were significant factors associated with surgical intervention, but not stone size <5 mm. Interestingly, in the present study, the incidence of surgical intervention was low in patients above 50 years of age with asymptomatic renal stones £5 mm and without a history of surgical intervention.…”
Section: Discussionmentioning
confidence: 50%
“…There is substantial variation in reported rates of surgical intervention from 7.1% to 40%, spontaneous stone passage from 3.1% to 29.1%, symptom development from 7.3% to 77.0%, and stone growth from 5.2% to 66.0% in patients with asymptomatic renal stones (Supplementary Table S4). 3,[13][14][15][16][17][18] This discrepancy is believed to be due to the difference in indications for surgical intervention, the difference in the definition for symptom development or stone growth, the length of follow-up, and the difference of the cohort in each study. The incidence of surgical intervention in our study is within the range of that from previous reports but is rather high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many series, the surgical intervention required in asymptomatic calyceal stones that ranged 19-25% [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the advantages of ESWL include shorter operative time and hospital stay in comparison to RIRS [20]. The need for long-term follow-up for asymptomatic calyceal stones and the finding that painless silent hydronephrosis developed in 2% of patients raise concern and mandate active treatment rather than the wait-and-see approach [17].…”
Section: Discussionmentioning
confidence: 99%